Silicon Photonics & High Performance Computing Proceedings of CSI 2015 (Advances in Intelligent Systems and Computing,, 2018)
This book comprises selected contributions to the Computer Society of India's annual convention. Divided into 10 topical volumes, the proceedings present papers on state-of-the-art research, surveys and succinct reviews, covering diverse topics ranging from communications networks to big data analytics, and from system architecture to cyber security. This volume focuses on silicon photonics & high performance computing, offering valuable insights for researchers and students alike.